Silver nanoparticles: Synthesis methods, bio-applications and properties. (3rd March 2016) - Abbasi, Elham; Milani, Morteza; Fekri Aval, Sedigheh; Kouhi, Mohammad; Akbarzadeh, Abolfazl; Tayefi Nasrabadi, Hamid; Nikasa, Parisa; Joo, San Woo; Hanifehpour, Younes; Nejati-Koshki, Kazem; Samiei, Mohammad
Abstract: Silver nanoparticles size makes wide range of new applications in various fields of industry. Synthesis of noble metal nanoparticles for applications such as catalysis, electronics, optics, environmental and biotechnology is an area of constant interest. Two main methods for Silver nanoparticles are the physical and chemical methods. The problem with these methods is absorption of toxic substances onto them. Green synthesis approaches overcome this limitation. Silver nanoparticles size makes wide range of new applications in various fields of industry. This article summarizes exclusively scalable techniques and focuses on strengths, respectively, limitations with respect to the biomedical applicability and regulatory requirements concerning silver nanoparticles.